Analysis of Human Trafficking in the Prostitution Industry in Indramayu: A Social and Legal Perspective - Ciek Julyati Hisyam; Sugeng Pujiyono (SocioEdu: Sociological Education, 2026)
This study aims to analyze the phenomenon of human trafficking occurring in the prostitution industry in Indramayu Regency, West Java, from a social and legal perspective. From a social perspective, this study focuses on the driving factors that cause individuals, particularly women and children, to become trapped in prostitution networks, which are often accompanied by exploitation and coercion. These factors include poverty, low levels of education, limited employment opportunities, and a lack of understanding of human rights. Furthermore, cultural aspects and social norms within the community also play a role in supporting these exploitative practices. From a legal perspective, this study assesses the effectiveness of law enforcement against perpetrators of human trafficking and the protection provided to victims. Although Indonesia has several regulations prohibiting human trafficking, the implementation of these laws and their enforcement in the field still face many obstacles. The method used in this research was a qualitative approach with in-depth interviews, participant observation, and documentation studies. Respondents included victims, perpetrators, the police, and social institutions involved in combating human trafficking and prostitution. The research findings indicate that human trafficking in the prostitution industry in Indramayu is driven not only by economic factors but also by the weakness of the legal system and the enforcement of justice. Furthermore, victims often lack adequate protection and are often trapped in a cycle of violence and exploitation. This research suggests the need for increased public awareness, improvements to the legal system, and an active role from the government and non-governmental organizations to eradicate human trafficking and provide better alternatives for victims.